The state of the pastoral economy of the Solon Evenki: Focusing on the logic of their communities - Nasunmenghe,; Yagi, Kohei (Advances in Social Sciences Research Journal, 2020)
Although organizations such as hamlets and clans have often been regarded as an impediment to modern development, they actually provide organizational principles that are indispensable in supporting modern economic development. In this paper, we describe livestock farming in the Solon Evenki in the Evenki Autonomous Banner in Hulunbuir area of China’s Inner Mongolia Autonomous Region in detail and then explain how the system changed due to the prohibition of nomadism and the roles communities played. The results are as follows. First, although the main business is daily with livestock farming, there are several sources of revenue and it is characterized by diverse and rich economic activities mainly on small-scale pastoralism. However, with the development of non-renewable resources like coal, this economic structure is being scaled up and simplified, so that temporary economic gain might come with the risk of long-term economic weakness. Second, looking at the actual use of the pastures, we see that there is no clear line between pasture and common land. As the partitioning off of land incurred significant transaction costs, local social relations functioned to regulate it in an ad-hoc manner.